One step beyond the lab and clinic: “walking the dementia conversation” - Zegarra-Valdivia, Jonathan Adrián; Aguzzoli-Peres, Fernando; Kornhuber, Alex; Arshad, Faheem; Paredes-Manrique, Carmen Noelia (Frontiers in Public Health, 2023)
Dementia research over the last 30 years has suffered the loss of millions of dollars in unsuccessful clinical trials in search of treatments. Although there are currently two promising drugs, the research is insufficient. The dehumanization of patients and the pressure to publish have promoted a decrease in the quality and usefulness of scientific research. One way to combat these problems is to return to the contact and closeness of those who put their faith in researchers. Fine-tuning the participation of patients with dementia and caregivers in research design and improving their connection and communication with researchers could positively contribute to the perspectives and strategies of scientists, generating a new and enriching vision. The Walking the Talk for Dementia showed that people can still live with dementia despite their diagnosis.Around 300 participated in the all-week "Santiago's Camino" symposium. People living with dementia, caregivers, healthcare professionals, activists, clinicians, and researchers participated in this event. The "Walking the Talk for Dementia" (WTD) event vividly demonstrated a strong commitment to upholding GBHI's core values of Authenticity, Fairness, Openness, Respect, Courage, and Empathy (A FORCE) to advance equity in brain health. These values provide clear guidance for their advocacy initiatives aimed at mitigating the global impact of dementia.Research and development are essential across scientific fields, especially in clinical contexts where involving patients and caregivers is critical. The WTD initiative exemplifies this by bringing together researchers, caregivers, and dementia patients on the Camino de Santiago in Spain.